PEMIKIRAN POLITIK KHALID MUHAMMAD KHALID - Musyafaah, Nur Lailatul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
This article discusses the Political Thought that Khalid Muhammad Khalid experience the duality of political thought. In the 1950s, when he wrote